Entrepreneurial Resilience: Gleaning Valuable Insights from Start-up Failures for a Path to Success - Karikari Amoa-Gyarteng (ZBW - Leibniz Information Centre for Economics; ZBW - Leibniz Information Centre for Economics, 2023)
This essay highlights key lessons for start-up success gleaned from the failures of other start-ups. It emphasizes the importance of conducting thorough market research, building a strong team and leadership, embracing adaptability, listening to customer feedback, and learning from failure. Through a commitment to excellence and a willingness to learn and adapt, entrepreneurs can navigate the road to start-up success and create a strong foundation for growth and sustainability. Ultimately, it is entrepreneurial resilience that sets successful start-ups apart from those that fall by the wayside.
Keywords: 330; Resilience; Start-Up